Pemanfaatan Limbah Bambu dan Ampas Tebu Sebagai Campuran Substitusi Serat dalam Pembuatan Plafon GRC (Glassfibre Reinforced Cement) - Rahmadi, Muhammad Ridho; Adil, Muhammad Naufal (Civil Infrastructure Engineering and Architectural Design, 2024)
The demand for ceilings in Indonesia continues to rise in line with large-scale infrastructure renovations aimed at supporting domestic economic growth post-pandemic. Ceilings serve a vital function as heat absorbers, ensuring rooms do not become overly warm. On another note, the utilization of waste in Indonesia remains considerably low, leading to environmental pollution and disruptions to the ecosystem. Among the waste that can be repurposed for building material innovations are bamboo and sugarcane, the latter being one of the primary ingredients for making sugarcane sugar (Saccharumofficinarum). The objective of this research is to devise an innovative substitute for fiberglass ceiling material that is both cost-effective and eco-friendly. This study encompasses various variations, such as A, B, C, D, and E. The fiber proportions for variation A are 100% glassfiber, B is 60% glass fiber and 40% bamboo fiber, C is 80% glass fiber and20% sugarcane fiber, D is 60% glass fiber, 30% bamboo fiber, and 10% sugarcane fiber, while E is 60% glass fiber, 10% bamboo fiber, and 30% sugarcane fiber. The expected outcome of this research is an innovative, ecofriendly, and more affordable ceiling material substitute. Simultaneously, it aims to take concrete steps to minimize environmental impact. The findings reveal that variation D, with proportions of 60% glass fiber, 30% bamboo fiber, and 10% sugarcane fiber, scored the highest in terms of flexural modulus strength at 38,787 kgf/cm2, a density value of 1.65 gr/cm3, and had a production cost that was IDR 189.00 cheaper compared to variation A or the conventional ceiling.